Direct Synthesis of Mixed-Metal Paddle-Wheel Metal-Organic Frameworks with Controlled Metal Ratios under Ambient Conditions - Lee, Giwook; Hwang, Jongkook (Inorganic Chemistry, 2023)
Currently, synthesizing mixed-metal metal-organic frameworks (MM-MOFs) in a single step remains a challenge due to the varying reactivities of different metal cations. This often results in the formation of mixtures of monometallic MOFs or MM-MOFs with nonstoichiometric metal ratios. A promising approach to overcoming this issue is the controlled precursor method, which uses prebuilt polynuclear complexes with structures similar to the secondary building units (SBUs) of the desired MOFs. In this study, we report that metal acetates can serve as natural prebuilt SBUs, enabling the controlled synthesis of MBDs ([M2(BDC)2DABCO]n, M = metal, BDC = 1,4-benzenedicarboxylic acid, DABCO = 1,4-diazabicyclo[2,2,2]octane) under ambient conditions. By exploiting the fact that metal acetates readily form soluble paddle-wheel dimers similar to the SBUs of MBDs, we achieve the direct synthesis of mixed-metal MBDs at room temperature. The metal ratios (Zn, Co, and Ni) in the resulting MBDs are controllable, and the production yields exceed 90%. The use of metal acetates facilitates the fast and uniform nucleation of MBDs, regardless of the metal cations involved. This similarity in nucleation rates leads to the formation of bimetallic and trimetallic MBDs with predefined metal ratios and homogeneous metal distribution while maintaining the quality of the MOFs. Importantly, this strategy offers an efficient pathway for synthesizing mixed metal MBDs using stoichiometric amounts of metal salts without toxic additives, high energy consumption, and complex synthesis steps.
Keywords: Ambient conditions; Direct synthesis; Metal acetate; Metal cation; Metal ratio; Metalorganic frameworks (MOFs); Mixed-metals; Paddle wheels; Secondary building units; Single-step